Analisis Ergonomi Dan Keamanan Tempat Duduk Penggunaan Crane Pengangkat Elektrik Dalam Proses Transfer Pasien Penyandang Disabilitas - Poesoko, Ayu Setyaning Sayekti; Setyono, Bambang; Chalifatullah, Fachrul Ramadhan (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
ABSTRACT Disability is a condition in which an individual experiences limitations or an inability to perform activities in ways that are considered normal by most people. These limitations are usually caused by impairments or a decline in the individual's abilities. As a result, the person may require assistance from others to manage daily life. This study aims to analyze ergonomic and safety aspects of the use of an electric lifting crane seat in the process of transferring patients with disabilities. The research employs the RULA method with weight variations of 40 kg, 60 kg, and 80 kg. The results indicate that the electric lifting crane in transferring patients weighing 40-60 kg received a score of 2, indicating minimal risk and no immediate need for improvement. Meanwhile, for patients weighing 80 kg, the device scored 3, indicating a low risk in the near future. The transfer belt pad for the wheelchair on the electric lifting crane is deemed appropriate according to the SNI standard (09-4663-1998), as no physical defects were found.